A novel design of rotary regenerative condensing heat exchanger for the dehydration from high humidity flue gas. (March 2019) - Wang, Limin; He, Yang; Tang, Chunli; Wang, Yikun; Che, Defu
Highlights: A regenerative condensing heat exchanger was proposed to dehydrate the flue gas. An analytical model and the corresponding calculation program were developed. The thermal characteristics of the RRCHE was examined. The RRCHE was more effective and economical than the FPTHE. Abstract: A rotary regenerative condensing heat exchanger was proposed for dehydration of the flue gas outflowing from the desulfurization tower in coal-fired power plant. An analytical model of heat and mass transfer processes in the regenerative condensing heat exchanger was developed. A calculation program was built by using an iterative solution technique to compute the heat transferred from flue gas to cooling air and the condensation rate of water vapor in the flue gas. The distributions of flue gas temperature, matrix temperature, water vapor mass fraction and condensate water mass were analyzed. The effects of matrix materials, operational and structural parameters of the rotor on the condensation efficiency were examined. The condensation efficiency from high to low for different matrix materials are in the sequence: SiC ceramic > carbon steel > fluorine plastic > Borosilicate Glass. Once the rotation speed, the height and radius of the rotor are larger than specific values, their changes are less effective on the condensation efficiency. Compared with the fluorine plastic tube condensing heat exchanger, the rotary regenerative condensing heat exchanger was more effective and economical on the whole volume and the capital cost to meet the same requirement of condensation efficiency.